Increased vegetation ground cover reduces water, sediment and phosphorus losses in Cambisol treated with swine slurry - Pessotto, Patrícia Pretto; Gatiboni, Luciano Colpo; Dall Orsoletta, Daniel João; Mumbach, Gilmar Luiz; Iochims, Daniel Alexandre (Revista de Ciências Agroveterinárias, 2021)
This study aims to evaluate the influence of the ground cover rate by crop residues and the rain time elapsed after the application of liquid swine slurry (LSS) under losses of water, sediments, and phosphorus (P). The study was carried out under a Humic Cambisols. Two areas were delimited: with and without the application of LSS. Each area was subdivided into four levels of crop residues: 5%, 35%, 65%, and 95%. Vegetable residues present in the area, from corn and black oat, were used. Three collecting gutters of 0.60 m² were installed in each subplot. Simulated rain was carried out on these, and the runoff volume collected for quantification and determination of losses. With LSS application, increase in the cover rate by crop residues reduces 0.3 mm h-1 the runoff volume and 1.67 mg m-2 reactive soluble P (H2O-P). The sediment losses in the first collection after the beginning of the rain were 23 times lower in the soil with 95% ground cover than in the soil with 5% ground cover. The loss of total P (total-P) decreases with the increase of the ground cover of the soil and increases in the same way with the increase of the time.